2016
DOI: 10.1038/ajg.2016.305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of National Institutes of Health Gastrointestinal PROMIS Measures in Clinical Practice: Results of a Multicenter Controlled Trial

Abstract: OBJECTIVE The National Institutes of Health (NIH) created the Patient Reported Outcomes Measurement Information System (PROMIS®) to allow efficient, online measurement of patient-reported outcomes (PROs), but it remains untested whether PROMIS improves outcomes. Here, we aimed to compare the impact of gastrointestinal (GI) PROMIS measures vs. usual care on patient outcomes. METHODS We performed a pragmatic clinical trial with an off-on study design alternating weekly between intervention (GI PROMIS) and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…A variety of decision aids has been developed and proposed to help patients understand diagnostic or treatment options . The assumption that technical information, provided in the friendly format of a decision aid, is all what is needed for people to make decisions, dismisses the value of the conversation and the essential bidirectional dimension of SDM.…”
Section: Tools and Simulation‐based Training To Promote Sdmmentioning
confidence: 99%
See 3 more Smart Citations
“…A variety of decision aids has been developed and proposed to help patients understand diagnostic or treatment options . The assumption that technical information, provided in the friendly format of a decision aid, is all what is needed for people to make decisions, dismisses the value of the conversation and the essential bidirectional dimension of SDM.…”
Section: Tools and Simulation‐based Training To Promote Sdmmentioning
confidence: 99%
“… Sources: Hargraves et al, Nicolai et al, Brezis et al, Tsulukidze et al, Barr et al, Almario et al, Little et al, and Krupat et al …”
Section: Tools and Simulation‐based Training To Promote Sdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Short outcome measures for 8 gastrointestinal symptom complexes were developed with good reliability and validity . Although the use of these domain‐specific PROMs was hypothesized to improve patient satisfaction, a recently performed trial compared the use of PROMIS with regular care and found no difference in patient satisfaction and shared decision making . However, several limitations should be considered including the poor response rate, lack of information about influence on clinic visit efficiency and frequency, cost‐effectiveness, and long‐term effects, which demonstrates the need for additional research …”
Section: Future Perspectivesmentioning
confidence: 99%